The Role of Toll-Like Receptor Signaling in the Progression of Heart Failure - Lili Yu; Zhiwei Feng (Mediators of Inflammation)
Medical systems worldwide are being faced with a growing need to understand mechanisms behind the pathogenesis of heart failure (HF) that is considered as a leading cause of morbidity and mortality around the world. Elevated levels of inflammatory mediators have been identified in patients with HF, which are primarily manifestations of innate immune responses mediated by pattern recognition receptors (PRRs). Toll-like receptors (TLRs), which belong to PRRs, are subjected to the release of pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) to generate innate immune responses. More and more emerging data indicate that TLR signaling pathway molecules are involved in the progression of HF. Herein, we present new data with regard to the activation of TLRs in the failing heart, focusing on TLR2, TLR3, TLR4, and TLR9, and suggest the potential use of TLRs in target therapy.